Impact of a congested match schedule on internal load, recovery, well-being, and enjoyment in U16 youth water polo players - Perazzetti, A.; Kaçurri, A.; Gjaka, M.; Pernigoni, M.; Lupo, C.; Tessitore, A. (Sports, 2025)
This study aimed to monitor internal load, well-being, and recovery status in U16 male water polo players during a congested competitive period. Fourteen athletes from an Italian club played 12 matches (seven friendly, five official) over 7 days. The internal match load was measured using the session-RPE method (s-RPE). Perceived enjoyment was measured with the Enjoyment Likert Scale (ENJ), while recovery and well-being were evaluated using the Perceived Recovery Scale (PRS) and the Hooper Index (HI), respectively. No significant main effects were found on s-RPE, PRS, and HI considering friendly and official matches. However, ENJ was significantly higher during official matches (p < 0.005). PRS values were significantly affected by daytime matches (p < 0.005), with better perceived recovery reported for morning matches. Linear mixed model analysis revealed significant associations between s-RPE and HI (p = 0.001), the fatigue item (p = 0.001), and the PRS (p = 0.004). These results suggest that as internal load increases, players experience higher fatigue and report lower recovery and well-being scores. Employing simple, non-invasive tools like the RPE, PRS, and HI can help coaches and support staff to identify early signs of overtraining or insufficient recovery, allowing for more individualized load management and injury prevention in youth water polo athletes.